Strategi Guru Pendidikan Agama Islam (PAI) dalam Mengatasi Kesulitan Belajar Siswa - Wahidin, Ade; Budi Heriyanto; Ira Rahmatussyahriyah; Riati Sri Hartini; Nazrin Ab Razak (Institut Muslim Cendekia, 2026)
This study is grounded in the prevalence of learning difficulties in Islamic Religious Education and Character Education, which arise from a range of internal and external factors. In response to these challenges, Islamic Religious Education teachers are required to adopt appropriate and effective strategies to ensure the achievement of learning objectives. The purpose of this study is to explore the strategies employed by Islamic Religious Education teachers in addressing learning difficulties among Grade VII students at SMP Informatika Bina Generasi Ciomas, Bogor. In addition, this study also aims to identify the supporting and inhibiting factors, as well as their implications. This research adopts a qualitative approach using a case study design. Data were collected through observations, interviews with teachers, the principal, vice principal, and students, and were further supported by documentation. The findings indicate that teachers employ several key strategies. First, they implement varied instructional methods, including small group discussions, reflective assignments, and direct practice of religious rituals such as ablution and prayer. Second, they provide additional instructional sessions, particularly for Qur’an reading and writing. Third, they apply a combination of scientific, contextual, emotional, and functional approaches to enhance students’ understanding. The effectiveness of these strategies is supported by several factors, including adequate school facilities, strong support from school leadership, active parental involvement, and positive interpersonal relationships between teachers and students. However, the study also identifies several inhibiting factors, such as low student motivation, limited interest in Islamic Religious Education, difficulties in reading the Qur’an, insufficient family support, negative peer influence, and excessive use of social media or digital devices. In conclusion, the strategies implemented by teachers have proven to be effective in helping students overcome learning difficulties while simultaneously fostering the development of their religious character.